2012
DOI: 10.1063/1.3687611
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic solutions for shocked resonant acoustic oscillations between concentric spheres and coaxial cylinders

Abstract: For resonant oscillations of a gas in a straight tube with a closed end, shocks form and all harmonics are generated, see Chester [“Resonant oscillations in a closed tube,” J. Fluid Mech. 18, 44 (1964)]10.1017/S0022112064000040. When the gas is confined between two concentric spheres or coaxial cylinders, the radially symmetric resonant oscillations may be continuous or shocked. For a fixed small Mach number of the input, the flow is continuous for sufficiently small L, defined as the ratio of the inner radius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Seymour et al. (2012) provided an estimate for the parametric range of the transition in the case of a spherical annulus and for a specific forcing amplitude. More recently Amundsen, Mortell & Seymour (2017) considered the analogous transition in the context of an open axisymmetric tube.…”
Section: Transition From Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Seymour et al. (2012) provided an estimate for the parametric range of the transition in the case of a spherical annulus and for a specific forcing amplitude. More recently Amundsen, Mortell & Seymour (2017) considered the analogous transition in the context of an open axisymmetric tube.…”
Section: Transition From Tomentioning
confidence: 99%
“…The same authors (Seymour et al. 2012) considered the case of nonlinear resonant oscillations of a gas contained between two concentric spheres or coaxial cylinders when shocks are present and the dominant first harmonic approximation is not valid. A nonlinear geometric acoustics approximation predicted shocked flows that are confirmed by numerical solutions for a range of – the slope of a cone.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Seymour et al [57] conducted research to describe shocked resonant oscillations between concentric spheres and coaxial cylinders when the dominant firstharmonic approximation is not valid. They explained how a nonlinear geometric acoustics approximation could predict shocked flows.…”
Section: Rms Was Investigated Numerically Bymentioning
confidence: 99%
“…One of the most important questions is what happens if the dominant first harmonic approximation is not valid. Recently, Seymour et al [57] have shown that a nonlinear geometric acoustics approximation predicts shocked flows between concentric spheres and coaxial cylinders. They compared the results with full numerical solutions and found good agreement.…”
Section: Shocked Wave Motionmentioning
confidence: 99%
See 1 more Smart Citation